2011
DOI: 10.1080/02755947.2011.591239
|View full text |Cite
|
Sign up to set email alerts
|

Site Fidelity and Movement of Eight Species of Pacific Rockfish at a High‐Relief Rocky Reef on the Oregon Coast

Abstract: We used acoustic telemetry techniques to study the movements of eight species of Pacific rockfish (genus Sebastes) inhabiting Siletz Reef, a high‐relief rocky reef complex on the Oregon coast. Our primary interest was evaluating potential residence times for rockfish species in small, no‐take marine protected areas (MPAs) like those recently designated for Oregon waters (337–1,502 ha). We tagged 6 black rockfish S. melanops, 31 canary rockfish S. pinniger, 9 yelloweye rockfish S. ruberrimus, 5 quillback rockfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Our model results showed that for all size groups and areas of occupancy, sablefish are extremely mobile relative to many demersal marine fish (e.g., Hannah and Rankin 2011). The implications of our analysis are that sablefish are more mobile than previously thought, and fish originally tagged in the west have longer lifetime movements than fish originally tagged in the east.…”
Section: Movementmentioning
confidence: 58%
“…Our model results showed that for all size groups and areas of occupancy, sablefish are extremely mobile relative to many demersal marine fish (e.g., Hannah and Rankin 2011). The implications of our analysis are that sablefish are more mobile than previously thought, and fish originally tagged in the west have longer lifetime movements than fish originally tagged in the east.…”
Section: Movementmentioning
confidence: 58%
“…35 km for the Willapa line). Other tag detections were obtained from arrays of receivers maintained by the authors in Puget Sound (Andrews et al , 2010) or by researchers studying coastal habitats and embayments along the Pacific Ocean coast of North America (Parker et al , 2008; Hannah & Rankin, 2011) (see Table I for details).…”
Section: Methodsmentioning
confidence: 99%
“…Still image from video lander footage at Stonewall Bank, Oregon, showing a view that is partially obstructed on the right by nearby rock with a yellowtail rockfish (Sebastes flavidus) visible in the left foreground and a yelloweye rockfish visible below it in association with crevice habitat. and Rankin, 2011;Love et al, 2002). Although small fish are generally harder to accurately identify from video footage, juvenile yelloweye rockfish have very distinctive striped markings (Fig.…”
Section: Discussionmentioning
confidence: 97%